Surface analysis of polymers electrically improved by plasma-source ion-implantation - Lee, Y; Han, S; Lim, H; Kim, Y; Kim, H (SPRINGER HEIDELBERG, 2002)
Inert-gas (Ar, Xe) and reactive-gas (O-2, N-2) plasma-source ion-implantation (PSII) treatment of PI, PET, PS-BD, and MPPO surfaces was performed at an ion energy of 30 keV to improve the electrical properties of the polymers. The effect of ion energy, treatment time, rf frequency, and power on the surface resistivity of polymer was investigated. Depending on ion energy, dose, and ion species, the surface resistivity of the film was reduced by several orders of magnitude. XPS, TOF-SIMS, and SEM were used to characterize MPPO surfaces treated by Ar-PSII and Xe-PSII. From these measurements it was found that the improvement in surface resistivity after PSII treatment was related to graphite carbon or crosslinked carbon-double-bond species formed on the surface.